Environmental Effect on Temperature Measurement in Natural Gas Network Balance. Issue 1 (April 2021) - Arpino, F.; Canale, L.; Cortellessa, G.; D'Alessio, R.; Dell'Isola, M.; Ficco, G.; Moretti, L.; Vigo, P.; Zuena, F.
Abstract: Accurate temperature measurements are essential for accounting and balancing natural gas in transmission and distribution networks. In fact, in order to convert the gas volumes measured at operational conditions into standard reference ones, the accurate knowledge of both the thermodynamic conditions of the gas (i.e. temperature and pressure) and its chemical composition is necessary. In the case of large flow-meters, even small measurement errors (e.g. deriving from difference between the ambient temperature and the temperature of the fluid) can become relevant in terms of "unaccounted for gas", especially when they do not find adequate compensation during the annual balancing of the network. To this aim it is necessary to carefully evaluate the systematic errors affecting temperature measurement which depend on instrumentation metrological characteristics as well as on thermo-fluid dynamic issues. In some cases, thermal insulation of the flow-meter and both upstream and downstream measuring stretches should be necessary. In this paper the authors present the results of an experimental study on the installation effects of temperature probes in closed conduits, performed at different operating conditions of natural gas transmission networks and aimed at estimating the typical random and systematic effects, and proposing optimal installation and operative solutions.